Niqab (Cadar) Dalam Perspektif Hukum Islam - Ulumuddin, Imam Khoirul (LP2M, 2020)
Abstract The conception of the niqab (veil) itself is a matter of ikhtilafiyah. Therefore, researchers are encouraged to study further by using the approach and study of the opinions of scholars about the use of veils for Muslim women. The purpose of this study is (1) To find out the meaning and characteristics of the niqab (veil) (2) To find out the history of the use of niqab (veil) for Muslim women (3) To find out the view of Islamic law on the use of niqab (veil) for Muslim women. This type of research is a literary (library research), because the data collected is obtained entirely from library data which is considered relevant to the research problem formulation and is a qualitative research category. The reason is, the data is presented in verbal form rather than data arranged in numbers. While this research approach uses a legal approach, which examines problems using Islamic law studies. The results showed that: (1) The veil can be understood as women's clothing covering the head and face, so that only the two eyes are visible. (2) The history of the use of the niqab (veil) was well known among the ancient nations, long before the advent of Islam, and was more attached to the Persians, especially in Iran. (3) The view of Islamic law on the use of niqab (veil) for Muslim women is a matter of khilafiyah, some are obligatory and some are not, each cleric has a strong argument, so that this becomes our option to choose, not even blame or even blaspheme the opinion that does not suit us. Keywords: Islamic law; khilafiyah; Niqab (veil)